A RANDOMIZED, DOUBLE-BLIND, PLACEBO-CONTROLLED TRIAL OF A CHINESE HERBAL SOPHORA FLOWER FORMULA IN PATIENTS WITH SYMPTOMATIC HAEMORRHOIDS: A PRELIMINARY STUDY - Man, Kee-Ming; Chen, Wen-Chi; Wang, Hwei-Ming; Chen, Huey-Yi; Shen, Jui-Lung; Chen, Lieh-Der; Tsai, Fuu-Jen; Chen, Yung-Hsiang; Yu, De-Xin; Chiang, Feng-Fan (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Dried flowers and buds of Sophora japonica (Huaihua) are used in China, Japan and Korea for treating haematemesis and bleeding haemorrhoids. This study compared the clinical safety and efficacy of a Sophora flower formula with a placebo for the conservative treatment of symptomatic haemorrhoids. The study was a prospective, double-blind, randomized placebo-controlled trial. The clinical effective rate, symptom score and the incidence of important clinical events were used as observation indices to evaluate the effect of the Sophora flower formula. The results showed that after 7 days of treatment, improvement was observed in 87.0% of the patients’ major symptoms in the Sophora flower formula group compared with 81.8% of those in the placebo group. After 14 days, 78.2% patients in the Sophora flower formula group were asymptomatic, whereas 40.9% of those in the placebo group exhibited residual symptoms. However, the difference between both groups was not statistically significant. As the bowel habits of the patients improved and as the patients took sitz baths, their symptoms improved drastically, regardless of the use of the Sophora flower formula. These findings indicate that the traditional Chinese Sophora flower formula is clinically safe; however, its effects on haemorrhoids need to be studied in a larger sample size and with different dosages. The present study results may be a potential clinical reference for physicians prescribing medications for patients with symptomatic haemorrhoids.